Identification of miRNAs related to osteoporosis by high-throughput sequencing - Huang, Jiachun; Yang, Haolin; Chai, Shuang; Lin, Yanping; Zhang, Zhihai; Huang, Hongxing; Wan, Lei (Frontiers in Pharmacology, 2024)
Background: Osteoporosis is a major health issue. MicroRNAs (miRNAs) play multiple roles in regulating cell growth and development. High-throughput sequencing technology is widely used nowadays.Objective: To screen for and validate miRNAs associated with osteoporosis.Method: Bone specimens from patients with (n=3) and without (n=3) osteoporosis were collected.High-throughput sequencing was used to screen for miRNAs that were then analyzed using volcano maps, Wayne maps, gene ontology (GO) analysis, and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis.Confirmation of the miRNAs was done using qRT-PCR. Results: The analysis of sequencing showed that there were 12 miRNAs that were down-regulated and five miRNAs that were upregulated in osteoporosis.GO and KEGG identified these miRNAs as being associated with bone metabolism.The qRT-PCR results showed that miR-140-5p, miR-127-3p, miR-199b-5p, miR-181a-5p, miR-181d-5p, and miR-542-3p exhibited a decrease of 2. 27-, 3.00-, 3.48-, 2.67-, 2.41-, and 1.98-fold (all P<0.05) in osteoporosis compared to controls. Conversely, miR-486-3p and miR-486-5p demonstrated an increase of 2.17-and 3.89-fold (P<0.05) (all P<0.05).This study utilized high-throughput sequencing to detect miRNAs that were expressed differently in individuals with osteoporosis.In osteoporosis, six miRNAs (miR-140-5p, miR-127-3p, miR-199b-5p, miR-181a-5p, miR-181d-5p, and miR-542) were found to have decreased expression, whereas two miRNAs (miR-486-3p and miR-486-5p) were found to have increased expression.The initial manifestation of various miRNAs might serve as predictive indicators and potentially anticipate the progression of osteoporosis.